Two Substitution Models in REE-LiZr2(PO4)3: Conditions of the Formation, Structure and Colour Characterisation - Gorodylova, Nataliia; Šulcová, Petra (Univerzita Pardubice, 2021)
In our work, the formation of the solid solutions (Li1-3xLaxZr2(PO4)3 and Li1+xZr2-xLax(PO4)3) according to the different substitution models has been studied. The solid solutions were prepared using two synthesis approaches: a polymerizable-complex method based on Pechini method (PM) and a solid state reaction (SSR). The phase composition of all samples were verified by XDR analysis. The colour properties of the samples were analysed by measuring spectral reflectance in the visible region of light (400-700 nm).
Dva substituční modely v REE-LiZr2(PO4)3:Podmínky vzniku, struktura a charakterizace barev
Keywords: LiZr2(PO4)3; Pechini method; solid state reaction; REE elements; LiZr2(PO4)3; Pechiniho metoda; reakce v pevné fázi; prvky vzácných zemín